Learning Obstacles in Third-Grade Mathematics Learning at SDN 1 Panjang - Cahya Rohim, Dhina; Putri Margaretha, Arienda; Rahmawati, Amalia; Manggalastawa (Education, Science, and Technology International Conference, 2024)
Mathematics is a means of solving problems from experience, knowledge and skills in everyday life so it needs to be mastered well. However, most students think that mathematics is a difficult subject, especially third grade students at SDN 1 Panjang. The perception that mathematics is a difficult subject is strengthened by the results of learning mathematics on multiplication of whole numbers which is below the KKM. This research aims to describe the learning obstacles by students and the factors that cause mathematical difficulties in multiplication of whole numbers. This research is qualitative research with the subject being the headmaster, third grade elementary school teacher and students at SDN 1 Panjang. The techniques used to collect data are observation, interviews, questionnaires and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The conclusion of this research is that the learning obstacles experienced by students include learning disorder, learning disability, learning dysfunction, teaching dysfunction, and under achiever. Meanwhile, the factors that cause obstacles to student learning consist of internal factors and external factors. Internal factors include negative attitudes in learning mathematics, low motivation to learn, body health, and sensory abilities. External factors include the lack of variation in teacher teaching, the use of learning media that is not optimal, the school infrastructure, and the family environment.